ELICITAÇÃO DE REQUISITOS NÃO FUNCIONAIS EM CONFORMIDADE COM POLÍTICAS DE QUALIDADE PARA APLICAÇÕES MÉDICAS - BASTOS FILHO, Francisco de Assis Menêzes (2007)
For several years, a lot of research is being done trying to find a solution for various problems concerning requirements engineering. Various approaches have pointed out that the requirements phase is the most important stage in the software development process. In general, requirements that are mistakenly elicited, analyzed and specified, gives rise to the development of low quality software. Non functional requirements gained little attention in the literature and are less understood but they are critical factors to the software development. When these requirements are badly elicited or not elicited at all, this gives rise to a difficulty in their treatment and their validation. Thus, we think that treating non functional requirements from the elicitation phase we contribute to a good software quality. This work deals with two aspects related with non functional requirements, namely how to elicit them and how to guarantee those requirements in conformity with a quality policy, even when new requirements or new technologies are adopted. As to attain this aim, we have elicited the requirements starting from a defined quality set necessary for medical applications. We defined a quality policy based upon these needs in such a way we could measure the conformity of non functional requirements definition specified in the requirements Document (RDs) with the desired quality, specified in the quality policy.